Анализ проблемы составления расписания занятий в вузе - Ячменев, Е. Ф. (Культура народов Причерноморья, 2014)
По результатам проведенного анализа существующих математических методик сформирована единая концепция составления расписания в учебных заведениях. Используя методы сравнения и аналогий, выявлены достоинства и недостатки существующих приемов составления расписания. В основе каждой методики лежит теория планирования. Анализ показал, что на данный момент не существует единой общепринятой модели, удовлетворяющей всем требованиям, предъявляемым к расписанию занятий в полном объеме. Определены группы ограничений к составлению расписания (строгие, нестрогие и необязательные). Рекомендуется использовать модель Попова Г.А. в качестве базовой модели для составления расписания занятий вуза. За результатами проведеного аналізу існуючих математичних методик сформована єдина концепція складання розкладу в навчальних закладах. Використовуючи методи порівняння і аналогій, виявлені переваги і недоліки існуючих прийомів складання розкладу. В основі кожної методики лежить теорія планування. Аналіз показав, що на даний момент не існує єдиної загальноприйнятої моделі, що задовольняє всім вимогам, що пред'являються до розкладу занять в повному обсязі. Визначено групи обмежень до складання розкладу (строгі, несуворі і необов'язкові). Рекомендується використовувати модель Попова Г.А. в якості базової моделі для складання розкладу занять вузу. Based on the analysis of existing mathematical techniques formed a unified concept of scheduling in schools. Using the methods of comparison and analogy, identified strengths and weaknesses of the existing techniques for scheduling. At the heart of each technique based on the theory of planning. The analysis showed that at the moment there is no single generally accepted model that satisfies all the requirements of the class schedule in full. The groups of constraints to the scheduling of (strict, lax, and optional). Features are as strict limitations: one session - one audience; one stream - one audience; one teacher - one lesson - one audience; capacity audience corresponds to the number of students in a group or in a stream; technical equipment must comply with the audience held in her classes; number of classes per week corresponds to a semester schedule. Lax - to schedule the flow should not be windows; the stream per day should be no less than two pairs. Not mandatory -minimizirovat transitions between buildings and groups of transitions need to be on a long break; consider securing audiences for departments. It is recommended to use the model Popov GA as a basic model for scheduling classes of high school.